Understanding Elementary Students' Use of Digital Textbooks on Mobile Devices: A Structural Equation Modeling Approach. (June 2019) - Wang, Xianhui; Xing, Wanli
The purpose of this study is to design a structural model explaining how elementary students use digital textbooks on mobile devices. This study extends the technology acceptance model framework, with self-efficacy, learning motivation, learning strategies, and parent education level as external variables. Results show that perceived usefulness was a significant mediating factor for students' actual usage of digital textbook on mobile devices. Self-efficacy and learning strategies influence self-reported actual usage through perceived usefulness and perceived ease of use. In addition, parent education level has a significant influence on students' self-efficacy and especially learning motivation. These findings have broadened research on technology acceptance with emphasis on a more learning-centered framework that focuses on the learners' characteristics and their unique contexts when using digital textbooks via mobile devices.